Psychosocial Safety Climate And Work-Related Outcomes Among Academicians In Malaysian Research Universities - Gan, Kia Hui (2022)
Drawing on the Conversion of Resources Theory and Job Demands-Resources Theory, this study intends to investigate the relationship between psychosocial safety climate and work-related outcomes (such as work engagement, job satisfaction, and organizational commitment). This study also intends to explore how job demands and job resources mediate the relationship between psychosocial safety climate and work-related outcomes (in terms of work engagement, job satisfaction, and organizational commitment). The hypotheses were tested on a sample of 484 academicians from Malaysian research universities. Data collected were analyzed using the SmartPLS software. Results revealed that psychosocial safety climate influences work-related outcomes. Both job demands and job resources were found to mediate partially the relationship between psychosocial safety climate and work-related outcomes.